Distribution of multidrug-resistant Salmonella spp. recovered from aquatic environment of Banda Aceh, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Suhartono S, Ismail YS, Aini Z. 2021. Distribution of multidrug-resistant Salmonella spp. recovered from aquatic environment of Banda Aceh, Indonesia. Biodiversitas 22: 881-886. The occurrence of pathogenic bacteria in an aquatic system might increase waterborne infections including salmonellosis. This might raise a concern related to the increasing pathogenic bacteria, including the multidrug-resistant Salmonella spp. in the two major rivers, namely Lamnyong and Krueng Aceh crossing the city of Banda Aceh, Indonesia. The objectives of the present study were to isolate and enumerate Salmonella spp. recovered from aquatic environment in Banda Aceh and to determine their antibiotic susceptibility. Bacterial enumeration was performed using most probable number (MPN) method followed by bacterial isolations using selective media Salmonella-Shigella Agar (SSA); whereas, antibiotic susceptibility test was conducted using a procedure as recommended by the National Committee for Clinical Laboratory Standards. There was no significant Salmonella spp. densities/mL of both locations (p = 0.200) although, on average there was about 441.67 Salmonella spp. MPN/mL in Krueng Aceh as opposed to 20.47 MPN/mL of Lamnyong river. There were 57 Salmonella spp. isolates recovered in the sampling sites, i.e. 38 isolates of Lamnyong and 19 isolates of Krueng Aceh. The results of antibiotic susceptibility tests showed that Salmonella spp. isolates recovered from Lamnyong and Krueng Aceh showed antibiotic resistance to azithromycin, tetracycline, and streptomycin. Moreover, Salmonella spp. isolates also showed high resistance to ofloxacin, ciprofloxacin, dan ceftriaxone. All Salmonella spp. isolates were classified as MDR with the number of isolates resistant to 4-6 antibiotics was 33 (57.9%), whereas those that were resistant to 7-9 antibiotics and over 10 antibiotics were 23 (40.4%%) and 5 (8.8%) respectively. The prevalence of MDR Salmonella spp. in the current study suggest that river remain the major reservoirs for the transmission of the pathogen in aquatic systems. An appropriate assessment and monitoring are necessary to reduce the potential health risks and to ensure water quality in the aquatic environment.
Keywords: Multidrug-resistant; Salmonella spp.; Aquatic environment